Context as a modifier of phraseological meaning - M. V. Harlamova (Vestnik MGIMO-Universiteta, 2014)
The article is devoted to the problems of actualization of phraseological units in the context of the French youth press. Due to the development of the connotative component of the meaning, phraseological units, as expressive means of the language, are often used in the process of communication to influence the addressee. The phraseological units with positive or negative estimation, expressing emotionally-evaluative attitude of the speaker towards the subject, influence the creation of the pragmatic direction of the utterance. Effected by the context, some changes take place within the structure of phraseological meaning. As the result the pragmatic direction of the text is increased. When a cliché is included into the context, the virtual (pragmatic) meaning is substituted by the actual (syntagmatic) meaning. Here, two variants of interaction of these meanings are possible. In the first case, the paradigmatic meaning and the syntagmatic meaning can coincide (thus, the phraseological unit is presented in its casual meaning.) In the latter case, the meaning of the cliché can be transformed under the influence of the context. It often leads to the divergence between paradigmatic and syntagmatic meanings. Thus, connotative-pragmatic characteristics of any phraseological unit can be defined by the context and it leads to : a) a cliché, losing its situational-evaluative feature (influenced by the context, the situational feature disappears and the cliché gets a positive or negative evaluation); b) the transition of the cliché to the "oppositely charged" field (phraseological units with negative connotation get positive connotation and vice versa); c) the intensification of phraseological meaning. The analyzed examples, proving the influence of the context on phraseological meaning, were taken from various French youth journals. (Okapi, le Monde des ados, Geo ado, Phosphore, Etudiant, Science & Vie Junior, Planète Jeunes).